Influence of the functional traits of seeds on germination dynamics and morphofunctional pattern of the seedlings - Anderson Polli; Mariza Barion Romagnolo; Luis Antonio de Souza; Lindamir Hernandez Pastorini (Acta Scientiarum. Biological Sciences, 2020)
Aiming to compare morphofunctional features related to dispersion and establishment of plants, this study evaluated seed biometry and biomass, as well as germination and emergence potential in eight plant species native to the Semideciduous Seasonal Forest. Biometric measurements and biomass of seeds were obtained with a caliper and a precision scale. Afterwards, they were subjected to a germination test in BOD chambers under constant temperature and 12 hours photoperiod, and sown in styrofoam trays containing organic substrate and sand, kept in full sunlight. Data from germination and emergence was subjected to cluster analysis, according to the functional morphotype of the seedling. Most species presented seeds with a rounded shape, uniform staining at the mature stage, varied coat consistency, two types of dispersal syndromes (anemochory and zoochory) and four morphofunctional patterns in developing seedlings (crypto-hypogeal-storers, crypto-epigeal-storers, phanero-epigeal-storers and phanero-epigeal-foliaceous). The species belonging to group I (Albizia niopoides, Cedrela fissilis, Pterogyne nitens and Randia ferox) have foliaceous photosynthetic cotyledons and group II (Cabralea canjerana, Eugenia pyriformis, Inga laurina and Poecilanthe parviflora) have a reserve cotyledon. Species of group I had higher means in the percentage and rate of germination, less variability and amplitude of days for seedlings emergence. On the other hand, species of group II showed higher mean values in seed biometry and biomass. Thus, seeds with foliaceous cotyledons have an optimized development because of luminosity, whereas seeds with reserve tend to have slower development, remaining at the seedling stage for a longer time.